Menggugat Stereotip Maskulinitas: Peran Ayah Tunggal dalam Film Rumah Aya (2021) - Sukmawati, Ni Luh Ayu (Jurnal Media dan Komunikasi, 2024)
This study criticizes the concept of "Housefather" that has released since 2021, which reflects changes in the construction of hegemonic masculinity in contemporary society. The dominant masculinity stereotypes have formed the gender dichotomy and resulted in the perception that men must be superior to women. However, this monolithic concept fails to encompass the various manifestations of masculinity that exist within diverse cultural contexts. This stereotype, often explained through the role of men as authoritative "heads of the household" who support the family and abstain from household chores, ignores a more complex and diverse reality. Through analysis of the film Rumah Aya (2021), this study responds to the idea that masculinity values can contribute to gender justice. Unlike popular films that usually focus on the mother's character, this film highlights a father's perspective and changes traditional stereotypes of masculinity. The main character, Bari, represents a unique construction of masculinity, one that differs from prevalent Western models of masculinity. In Teun A. Van Dijk's critical discourse analysis and Fluid Connell's concept of masculinity, this research shows a shift in the role of men from "head of the household" to "father of the household". These results point to a more flexible role for men, where they are no longer limited by their traditional role as breadwinners, but also participate in domestic and childcare tasks. This research, therefore, helps in expanding knowledge about variations in masculinity, particularly in local contexts, and breaking down the boundaries of rigid gender stereotypes. Keywords: Stereotype; masculinity; film; critical discourse analysis; gender roles.